Epidemiology of gastrointestinal parasites of dogs in four districts of central Ethiopia: Prevalence and risk factors - Kibruyesfa Bayou; Getachew Terefe; Bersissa Kumsa (PLoS ONE, 2025)
From February 2022 to April 2023, a cross-sectional study on dog gastrointestinal parasites was conducted in Bishoftu, Dukem, Addis Ababa, and Sheno, Central Ethiopia, with the aim of estimating the prevalence and evaluating risk factors. A total of 701 faecal samples were collected and processed using floatation and McMaster techniques. In dogs that were investigated, the overall prevalence of gastrointestinal parasites was 53.1% (372/701). Nematode (28.2%), cestode (8.4%), and protozoan (5.6%) parasite infections were detected in dogs in both single (42.2%) and combined (10.8%) infections. With respective prevalences of 16%, 9.8%, 5%, 3.9%, and 3.1% Ancylostoma spp., Toxocara canis, Dipylidium caninum, Giardia spp., and Taenia/Echinococcus spp. were the most common parasites. The prevalence of gastrointestinal parasites was significantly higher (P<0.05) in female dogs (73.8%, OR = 0.4), adult dogs (55.3%, OR = 0.4), dogs that were given raw food (57.9%, OR = 2.7), and dogs kept free outdoor (60.9%, OR = 2.4). The incidence of gastrointestinal parasites was also higher in dogs with diarrheal faecal consistency (89.1%, OR = 9.1) and dogs from highland areas (62.1%, OR = 1.8). In contrast, statistically significant variation in the prevalence of gastrointestinal parasites was not recorded among dogs of different breeds. The current study found that dogs in the studied locations had a high overall prevalence of gastrointestinal parasites. In conclusion, gastrointestinal parasites in dogs have the potential to pose a serious threat to public health, so addressing this issue requires a unified approach. Therefore, it is necessary to conduct detailed epidemiological and genetic research on dog parasites in vast study regions across various agro-ecologies zones and seasons in Ethiopia. Additionally, it is crucial to raise public awareness of the prevalence, effects on public health, and financial implications of dog gastrointestinal parasites in Ethiopia.